Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Siswa - Nurul Husda; Sriyanti Mustafa; Vernita Sari (Tautologi: Journal of Mathematics Education, 2024)
This study aims to determine the effect of learning independence on mathematics learning achievement of students of class X UPT SMA NegeriI 1 Parepare, while this type of research is a quantitative research using the Ex Post Facto approach. The population in this study were students of class X which consisted of 6 classes. The sample in this study was class X IPA 6 which amounted to 36 people, selected using a sampling technique called Cluster Random Sampling. The data of this research were obtained by using research instruments in the form of a learning independence questionnaire and documentation of learning achievement in the form of the odd semester report cards for the academic year 2021/2022. The data collection techniques used were questionnaire techniques and documentation techniques.The result of the descriptive analysis obtained an average score of 72.50 for learning independence and a standart deviation of 7.99. Students’ mathematics learning achievement is in the very high category with an average score of 85.44 and a standard deviation of 4.11. The results of the inferential analysis showed that there was a positive effect of learning independence on mathematics learning achievement of class X students of UPT SMA Negeri 1 Parepare with a significant value of 0.038 < 0.05.